Apoptosis and content of mobile lipid domains in human leukemia K-562 cells induced to differentiate by quercetin or dimethyl sulfoxide - Philchenkov, A.A.; Zavelevich, M.P.; Mikhailenko, V.M.; Kuyava, L.M. (Український біохімічний журнал, 2010)
The apoptotic index, cell cycle progression and caspase-3 activation in K-562 cells induced to differentiate by DMSO or quercetin have been studied. Quercetin treatment of K-562 cells was accompanied by cell cycle arrest in G2 /M and apoptosis with caspase-3 activation. In contrast, DMSO-induced differentiation was accompanied by the complete cell cycle arrest in G1 /G0 with negligible caspase-3 activation. In spite of the appearance of benzidine-positive cells and the decreased CD71 level in K-562 cells after exposure to quercetin, the analysis of 1H NMR spectra revealed the overall balance in favor of apoptosis, namely the increase in the content of NMR-visible mobile lipid domains and the decreased intensity of choline-containing metabolites. Визначали апоптотичний індекс, проходження клітинного циклу та активацію каспази-3 в клітинах K-562 в разі диференціювання, індукованого кверцетином або диметилсульфоксидом (ДМСО). Обробка клітин кверцетином супроводжувалась зупинкою клітинного циклу в фазі G2/M та призводила до апоптозу і активації каспази-3. Навпаки, в разі диференціювання, індукованого ДМСО, спостерігали повну зупинку клітинного циклу у фазі G1/G0 без активації каспази-3. Незважаючи на появу бензидин-позитивних клітин та зниження вмісту CD71 після інкубації з кверцетином, аналіз спектрів 1H ЯМР виявив баланс змін у бік апоптозу, а саме збільшення вмісту ЯМР-візуалізованих мобільних ліпідних доменів та зниження інтенсивності сигналу холін-вмісних метаболітів. Определяли апоптотический индекс, прохождение клеточного цикла и активацию каспазы-3 в клетках K-562 при индукции дифференцировки кверцетином или диметилсульфоксидом (ДМСО). Обработка клеток кверцетином сопровождалась остановкой клеточного цикла в фазе G2 /M и активацией каспазы-3. В противоположность этому при дифференцировке, индуцированной ДМСО, отмечали полную остановку клеточного цикла в фазе G1 /G0 без активации каспазы-3. Несмотря на появление бензидин-положительных клеток и снижение содержания CD71 после инкубации с кверцетином, анализ спектров 1H ЯМР выявил баланс изменений в сторону апоптоза, а именно, увеличение содержания ЯМР-визуализируемых мобильных липидных доменов и снижение интенсивности сигнала холин-содержащих метаболитов.